A Critical Review of Water Resources and Their Management in Bhutan - Muhammad Atiq Ur Rehman Tariq; Kelden Wangchuk; Nitin Muttil (Hydrology, 2021)
Bhutan is a small yet water-abundant country. The country suffers from frequent flooding and is lately experiencing a growing risk of localized droughts due to inappropriate water resource management and climate change. Such a situation calls for much more efficient use and management of water in Bhutan. This paper undertakes an extensive analysis of the country’s water resources for better planning and management of the available water resources. Bhutan can be divided into three zones, the Southern Foothills, the Central Inner Himalayas, and the Higher Himalayas. The top four leading industries of Bhutan are related to water, either directly or indirectly. The country at present is at a very early stage of development. The government has prioritized water resources management over recent years. Water for hydropower in Bhutan has been in focus as compared to that allocated for irrigation, industries, and environmental demand. The demand for water in Bhutan has also increased in the last decade due to population increase, changes in lifestyle, and economic advancements through tourism and hydropower projects. Climate variation, deteriorating water quality, frequent floods, and increasing urbanization threaten the sustainability of water resources. Water accessibility issues for settlements due to the country’s harsh geographical landscape is leading towards localized water scarcity. Serious attention to rainwater harvesting and groundwater recharge is required to address localized water scarcity issues.